Transgenerational and/or transcultural transformation of the reality of the village community: The Zduhać, the Zmijar or the (rural) esoteric - Trbojević Danilo (Glasnik Etnografskog Instituta SANU)
Throughout my years of researching demonological traditions, I have encountered mentions of certain individuals who were believed to possess, or who themselves claimed to have, specific powers. Most commonly, I came across zmijari (snake charmers). Interestingly, some of them were “descendants of zduhaći,” from whom they claimed to have “inherited their power.” Others retained the “powers” of their ancestors but directed their activities beyond their cultural or geographical environment, functioning as a kind of “rural esoterics.” A third group of interlocutors developed their “powers” through non-traditional sources of knowledge, expanding the method, purpose, and scope of their activities beyond the village. In this text, I analyse three (identity) models, each defined by a different source of knowledge or mastery of power, as well as by the method and specific goal of their practice. As I aim to demonstrate, these distinct identities reflect the hybridization of social and cultural reality, shaped by cross-cultural dialogue that in turn forms the habitus-or, in other words, the identities of my interlocutors today. I view these phenomena as a consequence of adaptation to the postmodern or even post-postmodern world, in which communities function as platforms for rethinking reality, the self, and the survival strategies of their members.